Aportes de una metodología lúdica al aprendizaje de los estudiantes que cursan la cátedra de morfofisiología en la facultad de cultura física, deporte y recreación (2019)
The project focused on establishing the contributions derived from a playful methodology in the learning of the students who study the Morphophysiology Chair in the Faculty of Physical Culture, Sport and Recreation of the Santo Tomás University, Bogotá Headquarters. The research had a mixed approach: of explanatory and microethnographic type, with a population sample composed of 24 students belonging to the course of 2D Morphophysiology 2018-1. In the quantitative phase an increase in the grades of the students in this chair was intended, but this was not significant for the study; while in the qualitative phase, contributions related to the importance of a motivating environment and that generated happiness in students' learning were identified, facilitating group cohesion and associative processes through play. As a conclusion it was obtained that the combination between traditional and playful education is an enhancer in the teaching-learning process.